IMPLEMENTASI PEDOMAN PENYELENGGARA PARIWISATA BERBASIS PRINSIP SYARIAH DI ERA MODERN: STUDI ATAS FATWA DSN-MUI NOMOR 108/DSN-MUI/X/2016 - Anand Yasmin, Muhamad; Aprilia, Alfia Eka; Basundari, Ninok; Waluyo, Waluyo (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Sharia tourism, which includes aspects of halal food, worship facilities, and governance is one of the strategic sectors in the development of the national sharia economy.This study aims to evaluate the extent to which the guidelines for organizing sharia-based tourism have been implemented in the Indonesian tourism industry, by referring to the DSN-MUI Fatwa Number 108/DSN-MUI/X/2016. Through a qualitative descriptive approach, data were obtained from literature studies, field observations, and interviews with tourism industry players. The results of the study indicate that the application of Islamic values ??in the tourism sector has made partial progress, but has not been fully integrated into the regulatory system and business practices. The main challenges include low sharia literacy, limited competent human resources, and minimal technical policy support. This study recommends strengthening derivative regulations, HR training, and digital-based promotional innovation as strategies for developing sustainable sharia tourism. This study contributes to the discourse on strengthening the sharia economy through an ethical and inclusive tourism sector.